THE PROBLEM OF TEACHER INTERACTION IN THE SYSTEM OF MODERN EDUCATION - Алпатова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The analysis of educational problems of interaction of the educational process at the university. Definitely the most common in modern educational practice educational paradigm. The features of the pedagogical paradigms in the context of professional activities high school teacher. The analysis of the results of research studying the positions of the educational process in educational interaction